What is Sarbanes-Oxley? - Lander, Guy P. (New York McGraw-Hill, 2004)
Everything you need to know about the Sarbanes-Oxley Act-- what it is, what your company must do to comply with SOA, and more. Written in clear, concise, and readable language, with helpful checklists.
Include Index
Keywords: United States -- Corporate governance--Law and legislation -- Corporations--Accounting--Law and legislation -- Directors of corporations--Legal status, laws, etc -- Disclosure of information--Law and legislation